A REVIEW ON GROWTH OF E-COMMERCE IN INDIA - Dr. Vandana Thakur (Innovative Research Thoughts, 2022)
The Indian economy's e-commerce sector is one of the most rapidly expanding in the world. For many industrialised and rising countries, the internet user base is lower than in India, despite the country's very high development rate. The Indian economy is heavily influenced by e-commerce. Currently, the nation is on the verge of a digital transformation. The total cost of owning and using a reliable internet connection has decreased as a result of the introduction of 4G services and the fall in data plan and data card/USB dongle pricing. Access to low-cost smartphones and the expansion of broadband Internet to the most rural areas would help to increase the number of internet users, therefore closing the gap between prospective online purchasers and real customers. The country's demographic dividend seems to be encouraging and promoting the rise of e-commerce as well. It is difficult for e-commerce companies that operate in a dynamic market to stay afloat in the face of fierce competition. The onus thus is on the companies to continually adapt and develop while offering a smooth and information-rich client experience. Researchers in this research set out to learn more about how e-commerce has evolved in India and how they expect it to continue to expand in the future.